The Relationship of Stunting Events with Intelligence Level in Elementary School Children at Air Beliti Health Center - Kurniati, Desi; Fajar, Nur Alam; Novrikasari, Novrikasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Stunting is a failure of growth and development experienced by children for a long time which can indicate a disturbance in the organs of the body, where one of the organs that is most rapidly damaged in nutritional disorders is the brain. Stunting is still a health problem in the world, especially in developing countries. The magnitude of the problem is due to the high prevalence of stunting, above the world standard of 20%. The incidence of stunting is caused by lack of nutritional intake during pregnancy and during growth. The purpose of the study was to determine the relationship between the incidence of stunting and the level of intelligence in elementary school children. This study used a cross-sectional design. The research population was elementary school children in grades 4, 5 and 6 of 5 elementary schools in the working area of the Air Beliti Health Center, as many as 156 children using a simple random sampling technique. The sample in this study was 85 with random sampling technique. Data were analyzed by univariate, bivariate using chi square test, and multivariate using linear regression test. The results obtained from the level of intellectual intelligence above the average of 67.1%, and children who did not experience stunting were 72.9%, the results of the hypothesis test showed a significant relationship between the incidence of stunting (p = 0.011) and the level of intelligence in elementary school children. The results of the study indicate that there is a relationship between the incidence of stunting and the level of intelligence of elementary school children. The results of the study indicate that there is a relationship between the incidence of stunting and the level of intelligence of elementary school children, parents pay more attention to nutritional intake in accordance with the needs of elementary school children because stunting events can affect the growth and level of intelligence in children, health center health workers in order to create innovations in stunting prevention, especially in elementary school age children by involving the school through UKS activities ( School health).